Prospective phenotyping of long-term survivors of generalized arterial calcification of infancy (GACI) - Ferreira, Carlos R.; Hackbarth, Mary E.; Ziegler, Shira G.; Pan, Kristen S.; Roberts, Mary S.; Rosing, Douglas R.; Whelpley, Margaret S.; Bryant, Joy C.; Macnamara, Ellen F.; Wang, Sisi; Müller, Kerstin; Hartley, Iris R.; et al. (Genetics in medicine, 2021)
Purpose Generalized arterial calcification of infancy (GACI), characterized by vascular calcifications that are often fatal shortly after birth, is usually caused by deficiency of ENPP1. A small fraction of GACI cases result from deficiency of ABCC6, a membrane transporter. The natural history of GACI survivors has not been established in a prospective fashion. Methods We performed deep phenotyping of 20 GACI survivors. Results Sixteen of 20 subjects presented with arterial calcifications, but only 5 had residual involvement at the time of evaluation. Individuals with ENPP1 deficiency either had hypophosphatemic rickets or were predicted to develop it by 14 years of age; 14/16 had elevated intact FGF23 levels (iFGF23). Blood phosphate levels correlated inversely with iFGF23. For ENPP1-deficient individuals, the lifetime risk of cervical spine fusion was 25%, that of hearing loss was 75%, and the main morbidity in adults was related to enthesis calcification. Four ENPP1-deficient individuals manifested classic skin or retinal findings of PXE. We estimated the minimal incidence of ENPP1 deficiency at ~1 in 200,000 pregnancies. Conclusion GACI appears to be more common than previously thought, with an expanding spectrum of overlapping phenotypes. The relationships among decreased ENPP1, increased iFGF23, and rickets could inform future therapies.